Unusual presentation of erythema elevatum diutinum in an HIV-positive man with dramatic response to dapsone. (November 2019) - Kaur, Maninder; Sahoo, Alok K; Gupta, Somesh
Erythema elevatum diutinum (EED) is a form of chronic leukocytoclastic vasculitis, which is known to occur in human immunodeficiency virus (HIV)-positive patients. Mostly, in the setting of HIV, it presents as plaques, nodules and occasionally as vesicles. We present a case of EED manifesting as annular plaques in an HIV-positive man, which was predominantly acral in distribution, involving the face also. After starting on dapsone, it disappeared completely in three days.